The effects of elevated atmospheric CO2 on the biological control of invasive aquatic weeds in South Africa - Baso, Nompumelelo Catherine (Rhodes University, Faculty of Science, Botany Department, 2020)
There has been a rapid increase in atmospheric CO2 concentration, from pre-industrial values of 280 ppm to more than 400 ppm currently, and this is expected to more than double by the end of the 21st century. Studies have shown that plants grown above 600 ppm tend to have an increased growth rate and invest more in carbon-based defences. This has important implications for the management of invasive alien plants, especially for the field of biological control which is mostly dependent on herbivorous insects. This is because insects reared on such plants have been shown to have reduced overall fitness. Nevertheless, most of the studies on potential changes in plant-insect interactions under elevated CO2 are based on agricultural systems, with only a limited number of these types of studies conducted on alien invasive weeds. However, climate change and invasive species are two of the most prevalent features of global environmental change. Therefore, this also warrants active research and experimental studies to better understand how these systems will be affected by future climates. Thus, the aim of this study was to investigate the effects of elevated atmospheric CO2 on the biological control of four invasive aquatic weeds (Azolla filiculoides, Salvinia molesta, Pistia stratiotes, and Myriophyllum aquaticum). These species are a threat to natural resources in South Africa but are currently under successful control by their biological control agents (Stenopelmus rufinasus, Cyrtobagous salviniae, Neohydronomus affinis, and Lysathia n. sp.). To achieve this, the selected plant species were grown in a three-factor experimental design in winter (CO2 X nutrients X herbivory), and another two-factorial design in summer (CO2 X herbivory). Atmospheric CO2 concentrations were set at ambient (400 ppm) or elevated (800 ppm), as per the predictions of the IPCC. As per my hypothesis, the results suggest that these species will become more challenging in future due to increased biomass production, asexual reproduction and a higher C: N ratio which is evident under high CO2 concentrations. Although the biological control agents were in some instances able to reduce this CO2 fertilisation effect, their efficacy was significantly reduced compared with the levels of control observed at ambient CO2. These results suggest that additional biological control agents and other management methods may be needed for continued control of these invasive macrophytes, both in South Africa and further afield where they are problematic.
Keywords: Aquatic weeds -- Biological control -- South Africa; Plants -- Effect of atmospheric carbon dioxide on; Atmospheric carbon dioxide -- Environmental aspects